HUBUNGAN PENGETAHUAN DENGAN KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET BESI (FE) DI KLINIK NIRMALA SAPNI KOTA MEDAN TAHUN 2021 - ELVI SEPRIANI (LP2MTBM MAKARIOZ, 2022)
Iron tablets (Fe) as a supplement given to pregnant women according to the rules should be consumed every day, but forvarious reasons such as poor knowledge of pregnant women, the side effects of tablets caused by these tablets can cause aperson to poorly adhere to the consumption of iron tablets (Fe) correctly so that the purpose of giving the tablet is notachieved. The purpose of this study is to find out the relationship of knowledge with the compliance of pregnant women intaking Iron Tablets (Ferossus) at Nirmala Sapni Midwife Clinic in 2021. The type of research used is descriptive analyticswith a cross sectional approach. The number of respondents as many as 46 pregnant women using total samplingtechniques. The data was analyzed using the Chi-square test. The results showed that 43.5% of respondents had sufficientknowledge about bezi tablets (Fe), and 52.2% of respondents obediently took iron tablets (Fe). There is a Knowledgerelationship with The Compliance of Pregnant Women in Taking Iron Tablets (Fe) value p = 0.000 (p<0.05) The conclusion ofthis study is that there is a significant relationship between Knowledge and Compliance of Pregnant Women in Taking IronTablets (Fe) at Nirmala Sapni Midwife Clinic in 2021.